E-MODULE ENTREPRENEURSHIP BASED ON MIND MAPPING AS A MEDIA OF STUDENT UNDERSTANDING - Arifin, Syamsul; Pratikto, Heri; Churiyah, Madziatul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
In the context of distance learning, educators face limitations in utilizing traditional learning media, prompting the need to explore alternative approaches for self-evaluation activities. This research focuses on the development of an offline desktop version of an entrepreneurial mind mapping tool as a learning medium. The objectives of this study are twofold: 1) to analyze the feasibility of an interactive learning medium based on mind mapping, and 2) to assess its practicality in terms of structure and implementation. Data collection involved documentation methods, interviews, review sheets, expert validation, and questionnaires. The study employed the 4D stages (define, design, develop, disseminate) to develop the product in an e-module format. The findings indicate that the developed learning medium is highly feasible and practical. It significantly enhances students' understanding compared to other learning media, as evidenced by the measured results. Students responded positively to the developed media, suggesting that interactive learning media based on mind mapping in entrepreneurship courses can effectively support student understanding, especially in the context of distance learning.